Barriers and enablers to providing community-based occupational therapy to people with functional neurological disorder: An interview study with occupational therapists in the United Kingdom. (April 2022) - Nicholson, Clare; Francis, Jill; Nielsen, Glenn; Lorencatto, Fabiana
Introduction: Occupational therapists have an integral role in the treatment of people with functional neurological disorder, yet there is evidence of variable implementation of occupational therapy in community settings. This study explored the barriers and enablers to delivering community-based occupational therapy to people with functional neurological disorder in the United Kingdom. Methods: Community-based neurological occupational therapists ( n = 10) with experience in functional neurological disorder were invited to complete semi-structured qualitative interviews. The interview schedule and analysis were based on the Theoretical Domains Framework, a behavioural science tool for investigating barriers and enablers to clinical practice. Data were analysed using a combined content and framework analysis approach. Findings: Important barriers to treatment included limited published information to guide practice, lack of professional role clarity and restricted multidisciplinary team working. Enablers included occupational therapists' dual training in physical and mental health and focus on activity engagement. Service provision, quality and access varied across geographical locations. Conclusion: Occupational therapists are uniquely placed to help people with functional neurological disorder; however, findings suggest that existing community service structures in many regions in the United Kingdom are inadequate and limit the quality of treatment that can be provided. Additional resources are required to support occupational therapy service provision in community settings.